The Concept of Self-Reliance in Community Development Initiatives in the Cameroon Grassfields (Nordic Journal of African Studies, 2003)
The Grassfields of Cameroon is a fertile ground for self-help efforts. This paper examines the resurgence role Village Development Associations (VDAs) are playing in national and community development. Community members are increasingly shouldering the adverse consequences of the economic downturn and the growing inability of the state to provide economic and social development by initiating, mobilising and galvanising their own resources in the quest for improving their standard of living. The reliance on indigenous technology and local human resources has led to overwhelming popular participation in community-driven development.